The health of Indigenous peoples living in Canada: Understanding distal, intermediate and proximal determinants of health - Hackett, Christina (2018)
Understanding how proximal, intermediate, and distal determinants of Indigenous peoples’ health in Canada, relate to the physical and mental health of First Nations, Métis, and Inuit, can shed light on how to allocate health-related resources to address well documented health disparities in these groups. This dissertation contributes to the literature by addressing two population-level quantitative research questions pertaining to Indigenous peoples’ physical and mental health, and a qualitative case study examining what factors maintain and improve Indigenous community health workers’ mental wellness and access to mental health supports. First, this thesis establishes a link between being Indigenous and health-related quality of life using multivariate regressions, as well as decomposition techniques. Second, the relationship between having an ancestor who survived the Residential School System, and five physical and mental health outcomes, controlling for determinants of health are estimated using multivariate ordered logistic and logistic regressions. Third, given that Indigenous self-government is an important determinant of health and wellbeing, an explanatory single-case study design is used to explore what factors maintain and improve, or create barriers to mental wellness and access to mental health supports for Indigenous community health workers in an Indigenous-governed health system. These chapters build on each other, and use a variety of methodological approaches, to identify if and to what degree observable determinants of health account for the physical and mental health of Indigenous peoples living in Canada. Substantively, this thesis evaluates empirically, the relationship between determinants of health and health outcomes for Indigenous peoples. Findings could be used to advocate for adequate and sustained investment in programs and services responsive to the contexts and needs of Indigenous men and women living in Canada. Methodologically, novel applications of statistical/econometric methodologies, furthers understanding of quantitative relationships examined with respect to Indigenous peoples’ physical and mental health at the population-level. In terms of a theoretical contribution, this dissertation contributes by lending further insight into the empirical relationships between determinants of Indigenous peoples’ health and health outcomes, and by introducing a framework for conceptualizing factors that strengthen mental wellness of Indigenous community health workers in remote Northern contexts in Canada. Thesis Doctor of Philosophy (PhD) First Nations, Métis, and Inuit make up 4.3% of the Canadian population and together represent the three distinct identities of Indigenous peoples living in Canada. Indigenous peoples’ experiences of colonization have had impacts on their physical and mental health. Additionally, experiences of colonization have also affected many determinants of Indigenous peoples’ health ranging from access to food and clean drinking water, to the availability of appropriate education, social, and healthcare services. The following chapters explore how certain experiences of being Indigenous in Canada are associated with physical and mental health outcomes, taking into consideration determinants of health. Even after controlling for all of the things known to be related to Indigenous peoples’ physical and mental health, and that are typically used to explain any differences in health between groups, there is still a difference in health outcomes between Indigenous and non-Indigenous peoples in Canada. There is also still a difference in physical and mental health outcomes between Indigenous adults with and without an ancestor who attended the Residential School System. The effects of colonization also influence Indigenous community health workers’ mental wellness, and access to mental health supports while living and working in a remote, Northern community.